Descriptive study of metabolic indicators in relation to pathological conditions: Case of diabetic nephropathy - LALMI Fatiha; HAMMOU Wissal (Université of Eloued, 2025)
Diabetes, both types, are among the most common chronic diseases in the world. They are characterized by high blood sugar levels resulting from a defect in insulin production or effectiveness within the body. Type 2 diabetes is more prevalent and has several effects that are not limited to high blood sugar levels, but also lead to chronic complications affecting various organs, most notably the kidneys. This condition is known as diabetic nephropathy, and may gradually develop into chronic kidney failure in advanced stages. The aim of this study is to determine the prevalence diabetic nephropathy and the extent of diabetes's impact on the kidneys. The study was conducted by collecting the results of 400 medical test reports chosen randomly. After that, a selection of 125 diabetic individuals, ranging from 12 to 92 years old was considered as the study sample based on the high blood levels of glycated hemoglobin. The data revealed that women are more likely to be affected by diabetes, with 70 women identified, representing 56% compared to 55 men, who make up 44%. In terms of age, the group most at risk of diabetes complications is those aged 72–62 years, representing 26%, followed by the 52–62 age group at 19%, and then the 72–82 age group at 18%. It was also found that the rate of kidney damage is the highest, with 80 out of 125 individuals affected, representing 64%, based on the results of blood urea and serum creatinine levels. Urine levels of microalbumine was used to determine the level of kidney damage. In the 80 cases of detected kidney damage, a number of 9 cases (11%) was noted as early stages of kidney damage verse 71 cases (89%) of progressed stages of kidney damage. In conclusion, chronically elevated blood sugar levels, lead to kidney damage and are the primary cause of diabetic nephropathy that need to be monitored and prevented.
Keywords: Type 2 Diabetes; Diabetic Nephropathy; Medical tests; Pathophysiology.; داء السكري من النوع الثاني، اعتلال الكلية السكري، الفحوصات الطبية، الفسيولوجيا المرضية